Resoluções de situações-problema de comparação multiplicativa: um olhar baseado na criatividade matemática - Almeida, Luana Cerqueira de (2022)
This research aims to analyze influence(s) of a teaching sequence, elaborated based on mathematical creativity, can bring to analyzes given by students in situations of multiplicative comparison with unknown relation. For that, we support the Theory of Conceptual Fields, we apply on the Multiplicative Comparison and the precepts of Mathematical Creativity. The study was developed with eight students from a public school. For the production of data worked with a teaching sequence containing nine problem situations in the Multiplicative Comparison axis, but, in this work, it analyzes how solutions given by students in two situations, in which the relationship is unknown. The results point to students who present a greater amount of correct solutions in situations where the expression is “more often” and the most used operation was subtracted, but, leads to error. In addition, this value does not respect the dimensions of mathematical creativity fluency is the dimension in which it is most shown when compared to flexibility and originality.